Effects of soil and water conservation interventions on some physico-chemical properties of soil in Hamelmalo and Serejeka Sub-zones of Eritrea - TESFAY, TUMUZGHI; OGBAZGHI, WOLDESELASSIE; SINGH, BALWAN (Journal of Soil and Water Conservation, 2020)
Extensive Soil and Water Conservation (SWC) interventions were carried out in Eritrea to arrest widespread land degradation, but their effect on soil physico-chemical properties has not yet been studied and hence, the present study was conducted to assess the influence of the SWC interventions on some soil properties in Hamelmalo and Serejeka sub-zones of Eritrea. Stratified sampling method was used to collect composite soil samples from conserved and non-conserved fields for comparison. The findings indicated that soil pH, moisture and clay contents were significantly higher in the conserved fields than in the non-conserved fields but it was not so for bulk density, electrical conductivity, organic matter, total nitrogen, extractable phosphorus and exchangeable calcium and magnesium. Thus, the study suggested that physical SWC measures should be integrated with biological and agronomic SWC measures and should be supplemented with good field management practices for better results.